Efisiensi Siaran RRI Medan Sebagai Penyaji Informasi Public Di Sumatera Utara - Hotmatua Paralihan; Nabila Assuhaila; Nurtia Asty Rahman; Novia Elisa; Adiva Amanda; Nada Hanifah Harahap; Rahmi Hilda Yanti Lubis (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
The study aims to analyze the effectiveness of Radio Republik Indonesia (RRI) Medan as a public information provider in the Utara region. The research uses content analysis, audience engagement, and technical performance evaluation. The results show that despite RRI Medan's success in providing public information, there is potential for improvement in local news and programs. This study contributes to understanding radio media's role in public information and providing specific recommendations for improving RRI Medan's effectiveness.